MAKNA TRILOGI CELENG KARYA SENI LUKIS DJOKO PEKIK - Thomas Edi Nugraha (Pascasarjana Institut Seni Indonesia Surakarta, 2010)
Djoko Pekik’s Trilogy Of The Wild Boars consist of three art works, namely First The 1996 Milk Of The Wild Boars King, second In The 1998 Indonesians Hunt Wild Boars, third The 1999 Flowerless and sad Telegram. The Trilogy Of The Wild Boars is Djoko Pekik’s is most expensive, monumental master piece. In his period / in his life time / in his generation. Based on such consideration, I can formulate the problems of the research as : What are the important aspect relating to the raise of the trilogy of the wild boars, meaning can be faund in the semiotic perspective, and why does the art collectors motivate to own his/Djoko Pekik’s art works ?.Based on the analysis of data, I can infer the important aspects relating to Djoko Pekik’s trilogy. The important aspects are the artist’s bitter past experiences, the meaning of the trilogy shows the falling down phases of the new order that can be seen on own Djoko Pekik’s art works is influenced by several factor, namely : Djoko Pekik’s art works have high economic value; The art collectors motivation can’t be separated from the strategy of Djoko Pekik’s self-image. From finding got by conclusion of about important aspect related to appearance painting of The Wild Boars. The aspect is bitter experience of past which have been experienced of by artist, while meaning of The Wild Boars to represent the phase depiction collapse the Orde Baru regime. Masterpiece of The Wild Boars push the collector enthusiasm because owning high economic value. The collector enthusiasm do not get out of the strategy of x’self image conducted by Djoko Pekik. Djoko Pekik’s strategy to increase his self-image is done by: 1. Developing good relationship among the artist, curator, and journalist as a publication need.2.Carriying out art exhibition.3. Raising the fresh, sensational ideas.4. Limiting the number of production of his art works.5. Reflecting his suffering past experiences through his at work.Keywords: Djoko Pekik, trilogy of the wild boars, the meaning analisys